2009
DOI: 10.1177/0959683608101397
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on buried soils and colluvial layers around Bronze Age burial mounds at Bornhöved (northern Germany): an approach to test the hypothesis of `landscape openness' by the incidence of colluviation

Abstract: The idea of open landscapes around prehistoric burial mounds is founded on their topographical position and findings of plaggen clots within the hills at some sites. We have investigated the surroundings of four Bronze Age burial mounds at Bornhöved (northern Germany) to test whether this assumed landscape openness enabled soil erosion and colluviation or not. The soils and colluvia within a watershed below the burial mounds were investigated in six large exposures and additional auger cores. The chronology is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 20 publications
2
25
0
Order By: Relevance
“…The studies of Neolithic buried soils, for example, under tumuli or ramparts, have already brought much interesting information (Hejcman, Gojda 2013;Barczi et al 2006;Breuning-Madsen et al 2009;Andrews, Fernandez-Jalvo 2012) about former landscapes. Comparison studies between buried and recent soils may answer questions connected with the past soil environment -as well as questions connected with the intensity of the anthropogenic impact (Wells 2000;Dreibrodt et al 2009;Elberling et al 2010;Horák, Hejcman 2013). During the last few decades the term "dark earth" has started to be commonly used.…”
Section: Introductionmentioning
confidence: 99%
“…The studies of Neolithic buried soils, for example, under tumuli or ramparts, have already brought much interesting information (Hejcman, Gojda 2013;Barczi et al 2006;Breuning-Madsen et al 2009;Andrews, Fernandez-Jalvo 2012) about former landscapes. Comparison studies between buried and recent soils may answer questions connected with the past soil environment -as well as questions connected with the intensity of the anthropogenic impact (Wells 2000;Dreibrodt et al 2009;Elberling et al 2010;Horák, Hejcman 2013). During the last few decades the term "dark earth" has started to be commonly used.…”
Section: Introductionmentioning
confidence: 99%
“…The analyses of colluvial sequences in northern Germany directly contradict this view of open landscapes around burial mounds. Dreibrodt et al (2009) found no evidence of colluviation in valleys proximal to a ceremonial complex during the period of burial mound building, in areas that would have been susceptible to erosion. Their interpretation was that of a largely wooded landscape, with clearings limited to the extent of the monuments themselves.…”
Section: The Character Of the Early Bronze Age Landscapementioning
confidence: 88%
“…Cummings and Whittle, 2003). This soft element of landscape may radically alter the interpretation of types of practice taking place at monuments, and there is a general assumption that burial monuments, such as barrows (raised burial mounds) were positioned in largely open landscapes so as to render them highly visible, described as the 'landscape openness' hypothesis by Dreibrodt et al (2009). It remains unclear, though, to what extent this hypothesis is correct, to what extent vegetation was actively 'managed', or whether vegetation was 'restructured' to create a particular type of landscape context for these monument complexes.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…We sampled between 10 l and 20 l of each layer of the colluvial exposures. The substrate was wet-sieved (mesh with 1 mm), air-dried and weighted before microscopical analysis (Dreibrodt et al, 2009).…”
Section: Charcoal Analysismentioning
confidence: 99%